Research on the Seam Formation Mechanism of Elliptical Bipolar Linear Directional Blasting Based on the SPH-FEM Coupling Method - Bo Wu; Hualong Li; Guowang Meng; Shixiang Xu; Jinglong Zhang; Yaozhong Cui (Shock and Vibration)
Rock mass blasting is a complex process that involves the coupling of both discontinuous and continuous media. This paper aims to reveal the dynamic failure process between adjacent boreholes under an elliptical bipolar linear charge structure using the SPH-FEM (smooth particle hydrodynamics and finite-element method) coupling algorithm numerical simulation method. The numerical simulation results are compared with the existing experimental results, which proves the rationality of the algorithm. According to the numerical simulation results, the shaped jet will first shock the hole wall and form a stress concentration zone that will guide the formation of cracks during the stress wave propagation process. In the case of double-hole blast loading, there is a tendency for cracks coalescence to develop between adjacent boreholes due to the superposition of stresses between the double holes and the increase in damage and plastic strain. The best blasting results will be achieved with this structure when the distance between adjacent holes is 110 cm. Finally, the superiority of elliptical bipolar linear blasting in engineering blasting was verified through field experiments. The results of this study provide a reference for subsequent applications of elliptical bipolar structures in the field of rock blasting.